Transient Luminous Events, into the Stratosphere and the Mesosphere, observed during violent thunderstorms lightning, are explained thanks to laboratory jets of photons in air, occuring during emission of Gravitational Quanta - POHER, Claude; POHER, Danielle (Advances in Social Sciences Research Journal, 2021)
Abstract : A Gravitational field emitter, as we patented in 2006, is composed of an “active” material squeezed between two metallic electrodes. The active material is superconducting, with conductive or insulating grains added inside, to get local electric fields during brief electric discharges made into that emitter. Along such a discharge, the emitter propels itself, by anisotropic re-emission of interacting Gravitational Quanta. These emitted quanta accelerate distant matter particles placed along their trajectory. With early YBCO superconducting material emitters, cooled down by liquid nitrogen, we observed systematically a bright emission of light into the bath. This light emission is caused by nitrogen molecules’ ionization by gravitational quanta push. In 2012, the partial superconducting behavior of natural Graphite, at room temperature, was discovered, so we built new emitters from Graphite. These shown the same propelling effect as the early ones made of YBCO, with a lower performance. Here we record and discuss light emission in the form of jets of photons, in air, at room temperature, and pressure, during strong electric discharges into Graphite based emitters. These results enhance the confirmation of predictions from our theoretical Quantum model of Inertia and Gravitation. They explain also the enigmatic Transient Luminous Events observed in the atmosphere over thunderstorms clouds.